2010
DOI: 10.1007/s12274-010-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Configuration-sensitive molecular sensing on doped graphene sheets

Abstract: We show by molecular dynamics simulations that configuration-sensitive molecular spectroscopy can be realized on optimally doped graphene sheets vibrated by an oscillatory electric field. High selectivity of the spectroscopy is achieved by maximizing Coulombic binding between the detected molecule and a specific nest, formed for this molecule on the graphene sheet by substituting selected carbon atoms with boron and nitrogen dopants. One can detect binding of different isomers to the nest from the frequency sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
3
0
1
Order By: Relevance
“…Wide graphene sheets were exposed to different types and amounts of molecules and molecular dynamics simulations were employed to treat these doping processes statistically. Our results are in agreement with similar ideas suggested by Russell and Kr al 27 in the understanding of the molecular configuration-sensitivity of graphene membranes. We demonstrate that the mass variation effect and information about the graphene-molecule interactions can be inferred through dynamical current-response functions and by means of the tunnelling current in a hypothetical (ac/dc)-NEMS device.…”
Section: Introductionsupporting
confidence: 93%
“…Wide graphene sheets were exposed to different types and amounts of molecules and molecular dynamics simulations were employed to treat these doping processes statistically. Our results are in agreement with similar ideas suggested by Russell and Kr al 27 in the understanding of the molecular configuration-sensitivity of graphene membranes. We demonstrate that the mass variation effect and information about the graphene-molecule interactions can be inferred through dynamical current-response functions and by means of the tunnelling current in a hypothetical (ac/dc)-NEMS device.…”
Section: Introductionsupporting
confidence: 93%
“…There have been many reports of the synthesis [15][16][17][18][19] and properties [13,20] of graphene and its applications in FETs [21,22], gas sensors [23,24], transparent electrodes [25], batteries [26,27], and hydrogen storage [28]. A number of studies have reported the use of graphene for biomolecular detection [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Similar doping strategies were proposed to achieve the selective docking of molecules. 59,60 We begin by examining the structural energetics of a graphene bilayer with a boron substitution in one layer and a nitrogen substitution in the other, as a function of the lateral offset between the dopants, within a 4 × 12√3 supercell. The ground state has the dopants in close proximity 58 as shown in Figure 2.…”
mentioning
confidence: 99%
“…While ab initio calculations of doped monolayer and bilayer 2D systems have been reported, the interaction between complementary dopants in adjacent layers has not yet been investigated as a mechanism of folding control. Similar doping strategies were proposed to achieve the selective docking of molecules. , …”
mentioning
confidence: 99%